Avaliação de parâmetros de resistência mecânica de material fresado estabilizado com cimento Portland, cal e rocha basáltica pulverizada para emprego em pavimentação - Rolim, Anderson Cristiano (2020)
The concern with environmental preservation together with economic growth is increasingly seeking the reuse of discarded materials in the construction industry as a source of raw material for new works. The recycling of discarded materials from the recovery or maintenance of highways can contribute to the economy and sustainability in road works. Besides, its reuse would collaborate in the reduction of the costs related to the transportation of raw materials and the decreased extraction of virgin materials from nature. Methods are being developed for the use of milled material originated from the removal of old claddings for application in new pavement layers, as shown in international literature Reclaimed Asphalt Pavement (RAP), which describes the application of milled material in structures of bases or sub-bases of pavements. In this way, the reuse of milled material from the maintenance of asphalt pavements is increasingly being the subject of research in the academic world, in search of its reuse. However, to be able to use that material in road works, a rational method of dosing mixtures, as the existing one for concretes, is necessary. In this way, this study aims to measure the influence of the amount of cement (percentage) and additions of quicklime (percentage), in a mixture of milled material with stone powder, evaluating their Void Index, Absorption and Specific Mass. Therefore, it is possible to obtain dosage parameters and to evaluate the influence of the relationship between voids and cementing material in the estimation of its resistance on the mixture of milled material and stone powder with different cement contents and also the addition of quicklime. The evaluations will be performed through laboratory tests: Tests for Characterizing (Particle Size Analysis, Extraction of Bitumen, Rice and Compaction), Unconfined Compressive Strength, Splitting Tensile Strength by Diametrical Compression, Flexural Tensile Strength and Resilient Modulus. All aforementioned trials also will be performed in the reference mixture composed of natural aggregates. The cement contents used in the study will be 4% and 5%, with quicklime added with its contents as 3% and 6%. The compaction of the specimens will be performed in standard, intermediate and modified energies, with the trials done in the 7th and 91st day curing period. Correlations will also be made between the mechanical properties with the characteristics of the mixtures through /% seeking to visualize resistances and modules for all studied mixtures. In this way, making it possible to apply the strokes in paving works, from the dosage of the cementitious material and its compaction.